Association of live microbes intake and risk of all-cause, cardiovascular disease, and cancer-related mortality in patients with chronic kidney disease - Debin Chen; Yongju Ye; Yining Li; Erxu Xue; Qijun Zhang; Youlan Chen; Jianhui Zhao (Renal Failure)
Background Chronic kidney disease (CKD) is a prevalent chronic, non-communicable disease. The long-term health effects of dietary live microbes, primarily probiotics, on CKD patients remain insufficiently understood. This study aims to investigate the association between dietary intake of live microbes and long-term health outcomes among individuals with CKD.Methods Utilizing the National Health and Nutrition Examination Survey (NHANES) database, Cox regression analysis assessed the association between medium and high categories dietary live microbe intake and health outcomes (all-cause, cardiovascular disease [CVD], and cancer-related mortality) in CKD patients.Results A total of 3,646 CKD patients were enrolled. During the follow-up period, 1,593 all-cause mortality events were recorded, including 478 CVD deaths and 268 cancer deaths. In the fully adjusted model, compared to CKD patients in the lowest quartile (quartile 1) of live microbes intake, those in quartiles 3 and 4 exhibited a 20% and 26% reduced risk of all-cause mortality, with hazard ratios (HR) of 0.80 (95% confidence interval, CI: 0.69, 0.94) and 0.74 (95% CI: 0.62, 0.90), respectively. Additionally, compared to those with low live microbe intake (quartile 1), higher live microbe intake in quartile 4 was associated with a 37% reduction in the risk of CVD mortality for CKD patients, with an HR of 0.63 (95% CI: 0.45, 0.88). Consistent results were observed in subgroup and sensitivity analyses. A significant negative association was observed between live microbe intake and the risk of all-cause mortality as well as CVD mortality in the CKD population, with a p-value for trend < 0.05.Conclusion Our study indicated that high dietary live microbe intake could mitigate the risk of all-cause and CVD mortality in CKD patients. These findings support the inclusion of live microbes in dietary recommendations, highlighting their significant roles in CKD.